(untitled) (Global Journal of Human-Social Science, 2023)
This case study was conducted in Chipinge district in Zimbabwe to investigate the cultural factors that influence the instruction of comprehensive sexuality education (CSE) in early grades, and subsequently identifies effective strategies to address these factors. The study employed a qualitative approach within an interpretivist paradigm. A purposive sample of ten parents and ten early grade teachers was selected to participate in the study. Data were collected through semi-structured interviews and analysed using a thematic approach. The language used in the instruction of comprehensive sexuality education (CSE) was found to be restrictive, impeding the effective delivery of CSE content due to cultural taboos surrounding the explicit mention of anatomical terms referring to genital organs. Teachers’ reluctance to teach CSE and their apprehension of potential victimisation by parents were identified as significant factors inhibiting the effective implementation of CSE in the early grades. Furthermore, the study revealed that within Zimbabwean culture, CSE is primarily perceived as education intended for individuals approaching marriage and adolescence.